S. Dube (2019). El archivo y el campo: historia, antropología, modernidad. México: El Colegio de México. 605 pp. - Curley, Robert (Estudios de Asia y África, 2020)
S. Dube (2019). El archivo y el campo: historia, antropología, modernidad. México: El Colegio de México. 605 pp.